Sergio Atzeni: The Retelling of the Mediterranean Sardinian Space - Dettori, Giovanni Maria (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
This article explores how Sergio Atzeni (1952-1995) deconstructs the crystallized image of Sardinia as an island outside time and space, untouched by the historical events occurring in the Italian Peninsula and the Mediterranean. Putting the author in dialogue with long-lasting representations of the island as found in travelogues and the Sardinian literary tradition, I investigate how the author in his latest works Il quinto passo è l’addio (1995) (The Fifth Step is a Farewell) and Bellas Mariposas (1995) (Beautiful Butterflies) creates a recounting of Sardinia. By challenging the fixity of a preconceived Orientalizing vision of the island, Atzeni engages in a totalizing representation of the insular space which expands the island storytelling into new settings, giving relevance to the previously neglected Sardinian urban space. My contribution, embracing Atzeni’s postcolonial framework as investigated by Birgit Wagner, introduces a discourse of geographical repositioning and remapping of the island. While the traditional discourse on the island remarked Sardinian isolationism and peripheral localization, I claim that the Sardinian author reinstates Sardinian Mediterranean-ess and openness through the representation of the urban environment of Cagliari transformed by Atzeni into a quintessential Mediterranean harbor city. In the rewriting of the island Atzeni presents Sardinia as connected to the Mediterranean Sea, no longer conceived as a barrier but rather as a water highway which for millennia has favored the transit of people, the mixing of cultures and languages that forged the island’s character. By repositioning the island at the center of the Mediterranean Sea, the island ceases to be a periphery and a marginal secluded insular territory. Thus, the island’s cultural and linguistic diversity embodies in Atzeni the intrinsic nature of the Mediterranean space that opposes openness to the closeness of the Sardinian borderland narration. I state that the novelty of his works is the introduction of a contemporary and multicultural image of the island in the Sardinian literary canon, more representative of the complexity of Sardinian historical past and society. By representing a multifaceted multicultural and multilingual society, he conceives literature as a place where cultural and linguistic diversity meets anticipating contemporary Italian multiculturalism.